The association between sex hormone-binding globulin and type 2 diabetes in Nigerian men - Fayefori M. Abbiyesuku; Augustine N. Agbakwuru; Olatunbosun O. Olawale (AOSIS, 2013)
Background: Epidemiological studies have shown that sex hormone-binding globulin (SHBG) has a role in glucose homeostasis in both men and women. However, a prospective study on Japanese-American subjects concluded that SHBG was not a significant risk factor in either men or women, suggesting ethnic differences. We were not aware of any evaluation of SHBG in subjects of African ancestry. Objectives: We investigated the association between SHBG and insulin resistance in type 2 diabetic diabetic men in a hospital in Nigeria. Method: Forty-eight male subjects with type 2 diabetes and 20 non-diabetic male subjects were recruited in this cross-sectional hospital-based study by the convenient sampling method.Height and circumferences around the waist and hip were measured to the nearest 0.5 cm and the waist-hip ratio was calculated from this measurement. Weight was measured and body mass index was calculated. Fasting plasma glucose concentration was measured by the glucose oxidase method with a between-run coefficient of variation of 3%. Insulin and SHBG were measured by means of enzyme-linked immunosorbent assay (ELISA). Results: There was a statistically-significant difference between test results for the diabetic and non-diabetic patients. The mean SHBG concentration was higher in the non-diabetic group (42.2 nmol/L) than the diabetic group (30.5 nmol/L). A significant inverse association between insulin resistance and SHBG was observed (r = 0.353, p < 0.015). Conclusion: This study supported earlier observations that a significant inverse correlation exists between SHBG and insulin resistance and provides evidence that the relationship may extend to type 2 diabetic men of African ancestry in Nigeria.